The synthetic cathinones MDPHP and MDPV: Comparison of the acute effects in mice, in silico ADMET profiles and clinical reports - Marta, Bassi (2024)
The 3,4-methylenedioxy-alpha-pyrrolidinohexanophenone (MDPHP) is a synthetic cathinone closely related to 3,4-methylenedioxypyrovalerone (MDPV), one of the most common synthetic cathinones present in the “bath salts”. MDPHP has recently gained attention due to increasing seizures and involvement in human intoxications which occurred in Europe and Italy in the last years, but currently there is a lack of information about its pharmaco-toxicological effects. With the aim at filling this gap, the present study is endeavoured to (i) evaluate the effects of acute administration of MDPHP (0.01–20 mg/kg; i.p.) on behaviour, cardiorespiratory and cardiovascular parameters in CD-1 male mice, comparing them to those observed after administration of MDPV; (ii) predict the ADMET profile of the two analogues using the Plus ADMET Predictor®; (iii) present clinical data related to MDPHP and MDPV-induced intoxications recorded between 2011 and 2023 by the Pavia Poison Control Centre (PCC) − National Toxicology Information Centre (Istituti Clinici Scientifici Maugeri, IRCCS Pavia, Italy). Our results substantiated that MDPHP and MDPV similarly affect sensorimotor and behavioural responses in mice, importantly increased locomotion and induced aggressive behaviour, and, at higher dosage, increased heart rate and blood pressure. These findings are in line with those observed in humans, revealing severe toxidromes typically characterized by Central Nervous System (CNS) alterations (behavioural/neuropsychiatric symptoms), including psychomotor agitation and aggressiveness, cardiovascular and respiratory disorders (e.g. tachycardia, hypertension, dyspnoea), and other peripheral symptoms (e.g. hyperthermia, acidosis, rhabdomyolysis).